Outcomes of Transcatheter Aortic Valve Replacement in Patients With Bicuspid Aortic Valve Disease: A Report From the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry. Issue 13 (31st March 2020) - Halim, Sharif A.; Edwards, Fred H.; Dai, David; Li, Zhuokai; Mack, Michael J.; Holmes, David R.; Tuzcu, E. Murat; Thourani, Vinod H.; Harrison, J. Kevin; Brennan, J. Matthew
Abstract : Background: Patients with bicuspid aortic valve (AV) stenosis were excluded from the pivotal evaluations of transcatheter AV replacement (TAVR) devices. We sought to evaluate the outcomes of TAVR in patients with bicuspid AV stenosis in comparison with those with tricuspid AV stenosis. Methods: We used data from the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry (November 2011 through November 2018) to determine device success, procedural outcomes, post-TAVR valve performance, and in-hospital clinical outcomes (mortality, stroke, and major bleeding) according to valve morphology (bicuspid versus tricuspid). Results were stratified by older and current (Sapien 3 and Evolut R) generation valve prostheses. Medicare administrative claims were used to evaluate mortality and stroke to 1 year among eligible individuals (≥65 years). Results: After exclusions, there were 170 959 eligible procedures at 593 sites during the specified interval. Of these, 5412 TAVR procedures (3.2%) were performed in patients with bicuspid AV, including 3705 with current-generation devices. In comparison with patients with tricuspid valves, patients with bicuspid AV were younger and had a lower Society of Thoracic Surgeons Predicted Risk of Operative Mortality score. When current-generation devices were used to treat patients with bicuspid AV, device success increased (93.5 versus 96.3; P =0.001) and the incidence of 2+ aortic insufficiency declined (14.0% versus 2.7%; P <0.001) in comparison with older-generation devices. With current-generation devices, device success was slightly lower in the bicuspid (versus tricuspid) AV group (96.3% in bicuspid versus 97.4% in tricuspid, P =0.07), with a slightly higher incidence of residual moderate or severe aortic insufficiency among patients with bicuspid AV (2.7% versus 2.1%; P <0.001). A lower 1-year adjusted risk of mortality (hazard ratio, 0.88 [95% CI, 0.78–0.99]) was observed for patients with bicuspid AV versus patients with tricuspid AV in the Medicare-linked cohort, whereas no difference was observed in the 1-year adjusted risk of stroke (hazard ratio, 1.14 [95% CI, 0.94–1.39]). Conclusions: Using current-generation devices, procedural, postprocedural, and 1-year outcomes were comparable following TAVR for bicuspid AV versus tricuspid AV disease. With newer-generation devices, TAVR is a viable treatment option for patients with bicuspid AV disease. Abstract : Supplemental Digital Content is available in the text.